Are Developing Countries Better Off Spending Their Oil Wealth Upfront? - Takizawa, H. (IMF Working Papers; Working Paper ;, 2004)
We question the conventional view that it is optimal for government to maintain a stable level of spending out of oil wealth. We compare this conventional policy recommendation with one where government spends all of its oil revenues upfront, at the same rate as oil is extracted. Using a neoclassical growth model with positive external effects of public spending on consumption and productivity, we find that, if the economy is growing along the steady-state balanced path, the conventional view is validated. However, if the economy starts with a lower capital stock, the welfare ranking across two policies can be reversed.